Maquiavel e a corrupção: doença e remédio - Castro, Lucas da Silva (2012)
The present dissertation sought to reflect upon the corruption problem present in the republican thought of Florentine Republic secretary. For the author, the historical experience of Rome Republic in Antiquity was the adequate source of imitation as well as inspiration to reach Machiavelli s greatest daytime dream: the Italian political unification. In this work, we tried to reunite Machiavelli s many speeches on corruption, relating this problem to his natural and unavoidable trait, with the rising of private life, to law and order construction. At the same time, we investigated the relation between corruption and religion, as well as corruption and education and how such problems were related to external contacts set out by one specific republic. Based on this, it is possible to affirm that when Machiavelli focuses on corruption, he believes it as sickness, and then seeks the remedies to heal it. As the author points out, although such remedies are of diverse nature, they demand a high responsibility from citizens, so that, as republic natural and unavoidable conflicts develop, they are able to force the use of the remedies, preparing the political conflicts to the republic freedom enhancement.